2017
DOI: 10.1093/ejcts/ezx222
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal adenocarcinoma has a higher risk of lymph node metastasis than squamous cell carcinoma: a propensity score-matched study

Abstract: Cases of oesophageal adenocarcinoma had a higher risk of lymph node metastasis than did those with SCC in this series, which indicates that different therapeutic modalities should be applied for these 2 different malignant entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…We applied multivariate logistic regression analysis to explore potential predictors of LN metastasis (both intrapulmonary/hilar and medisatinal LNs) for these patients, which was based on our discretion by adding all clinically relevant variables. Moreover, we further performed PSM analysis using the PSMATCHING 3.04 and R-2.15.1-win software as previously described 16 to further validate our results based on well-matched cohorts. The following covariates were used for matching: gender, tumor size, histology, tumor differentiation and consistency.…”
mentioning
confidence: 93%
“…We applied multivariate logistic regression analysis to explore potential predictors of LN metastasis (both intrapulmonary/hilar and medisatinal LNs) for these patients, which was based on our discretion by adding all clinically relevant variables. Moreover, we further performed PSM analysis using the PSMATCHING 3.04 and R-2.15.1-win software as previously described 16 to further validate our results based on well-matched cohorts. The following covariates were used for matching: gender, tumor size, histology, tumor differentiation and consistency.…”
mentioning
confidence: 93%
“…[1] In pathology, esophageal cancer mainly consisted of esophageal adenocarcinoma (EA) and esophageal squamous cell carcinoma (SCC). [2] Despite of the advancement of therapeutic strategies, the prognosis of esophageal still remains dismal with a 5-year survival rate of about 15% to 34%. [3] Therefore, investigation on novel potential medications that have anticancer effects for esophageal cancer seems to be greatly important, which might help improve the survival of esophageal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reveal significant differences in LNM between esophageal adenocarcinoma and ESCC. According to a propensity matching study by Deng et al , esophageal adenocarcinoma was associated with a higher number of positive lymph nodes and a higher rate of LNM than those of EC ( 15 ). Besides, Rice et al showed that esophageal adenocarcinoma was more prone to LNM than ESCC ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is noteworthy that most researchers do not apply different standards of LND scope and number for different tumor types. However, studies have shown that esophageal adenocarcinoma and ESCC possess different characteristics in lymph node metastasis (LNM) ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%